Tingkat Pengetahuan Petani dalam Penggunaan Pupuk Organik dan Penerapannya pada Budidaya Tanaman Padi Sawah (Kasus di Subak Penarungan, Kecamatan Mengwi, Kabupaten Badung) - I WAYAN BUDI ARTAWAN; NI WAYAN SRI ASTITI; WAYAN SUDARTA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Farmers Knowledge Level in the Use of Organic Fertilizer and Its Applicationin Rice Cultivation (Case in Subak Penarungan, Sub-District of Mengwi,Badung Regency) Public attention to the issue of agriculture and the environment in recent years haveincreased as a result of a big negative impact on the environment, compared with itspositive impact on increasing the productivity of agricultural crops. This encouragesseveral regions to hold organic farming. Organic farming is a natural farming whichin practice trying to avoid the use of chemicals and fertilizers that are poisoning theenvironment with the aim to obtain a healthy environmental condition.This studyaims to determine (1) the level of farmers' knowledge on organic fertilizer; and (3)the application of organic fertilizers by the farmers in the cultivation of lowland rice.The research was conducted at the Subak of Penarungan, Mengwi Sub-District ofBadung Regency. The choice of research location was conducted by purposivesampling. The population of the research was the active members of Subak ofPenarungan totaling of 167 people. The sample size was determined by using theformula of Slovin, so that the number of respondents was 63 people.This researchuse method analysaize descriptive qualitative. The results showed that farmers'knowledge about organic fertilizers can be categorized in the high category withachieving a score of 3.41. However, the application of organic fertilizer by thefarmers is classified in the medium category by achieving a score of 3.05. Based onthe results of this study can be suggested farmers as actors should be more activedoing weeding and want to optimize the use of organic fertilizer as recommended bythe extension. Because the use of sustainable organic fertilizer for the future will givea big influence in soil fertility, quality and not damage the environment.